An Indirect Method to Estimate Total Fertility Rate on the Basis of the Moments of Age Distribution of Women in Reproductive age - Singh, Brijesh P; Sing, Sandeep; Ranjan Chaurasia, Aalok (International Journal of Scientific Research and Management (IJSRM), 2021)
Total fertility rate (TFR) is the universally used indicator to measure and monitor fertility transition and population stabilization. Calculation of TFR requires data on births by age of woman. In the absence of these data, several indirect methods have been proposed to estimate TFR but their application is limited to specific period and place. This paper deduces a simple regression method for estimating TFR based on the current age distribution of women in reproductive age. The method can be used to estimate TFR at local level and for different sub-groups of the population.